2011
DOI: 10.1590/s0004-282x2011000400018
|View full text |Cite
|
Sign up to set email alerts
|

Headache among medical and psychology students

Abstract: Headaches occur frequently and thus are a key component of sociocentric medical education. Objective: To study headaches among students of medicine and psychology in a single university. Method: This was a questionnaire-based survey of a cohort of students of medicine and psychology. Results: The overall lifetime prevalence of headache was 98% and over the last year, 91%. Tensional headache accounted for 59% and migraine 22% in medicine; and 48.5% and 32% respectively in psychology. Forty-five percent reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
4
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 14 publications
3
25
4
11
Order By: Relevance
“…We found that the prevalence of migraine in our cohort is higher compared to other international studies. The prevalence of migraine among medical students reported to be 33.8% in Nairobi [13], 22% in Brazil [12], 14.1% in Nigeria [10], 13.1% in South East Nigeria [22], 12.6% in Turkey [6], 12.2% in in Oman [11] and 7.14% in the Southeast of Iran [23]. Most of our students were females 70.4% which could explain the higher frequency of migraine in our study compared to others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the prevalence of migraine in our cohort is higher compared to other international studies. The prevalence of migraine among medical students reported to be 33.8% in Nairobi [13], 22% in Brazil [12], 14.1% in Nigeria [10], 13.1% in South East Nigeria [22], 12.6% in Turkey [6], 12.2% in in Oman [11] and 7.14% in the Southeast of Iran [23]. Most of our students were females 70.4% which could explain the higher frequency of migraine in our study compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of migraine among medical students ranges from 11 to 40% worldwide [1,12,13]. The epidemiology of migraine among medical students is of a particular interest since migraine is the most common type of headache in young adults [6] and its frequency has been increased during students educational years of study [14].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of migraine has been reported to be between 12.4 and 21.9 % among university students in Turkey [1, 2, 19]. However, the prevalence of migraine among medical students reportedly ranges from 11 to 40 % worldwide [3, 28, 29]. A higher prevalence has been reported in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although migraine is also prevalent among medical faculty, health sciences, and psychology students, previous studies have not adequately assessed comorbid psychiatric conditions and personality traits in this specific population [28, 29]. Researchers have reported the prevalence of migraines using self-reporting instruments without performing neurological evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…(12) The results showed a prevalence of 22% for migraine, but the main subtypes of migraine were not differentiated, such as: with or without aura. Demonstrating that these results corroborate with the present study, in which a prevalence of 21% for migraine without aura was found in the academics of the Physiotherapy course.…”
Section: Discussionmentioning
confidence: 93%